REPRESENTAÇÕES SOCIAIS DA VIOLÊNCIA NAS PALAVRAS E ATITUDES DE JOVENS ESCOLARES - Dalmolin, Indiara S.; Costa, Marta C. d.; Silva, Ethel B. d.; Santos, Alice d. C. J. M. d.; Silva, Cristiane M. d. (Salão do Conhecimento, 2013)
Resumo